2017
DOI: 10.26858/eltww.v4i1.3195
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Teacher Talk toward Students’ Attitude to Speak English

Abstract: This research aimed at identifying the formal and interactional features of teacher talk in the classroom interaction during teaching and learning process. The research employed mixed methods research design. In this case, the researcher  applied QUAN-qual model. The subjects consist of two English teachers and the fourth year students of English Education Department of Tarbiyah and Teacher Training Faculty at State Islamic University of Alauddin Makassar. The researcher collected the data using interview, que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The research by Munawir (2017) entitled "the influence of teacher talk toward students' attitude to speak English" also found that the teachers provided interactional feedback when addressing students in the classroom. In terms of attitude, the students had a positive attitude toward lecturer talk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research by Munawir (2017) entitled "the influence of teacher talk toward students' attitude to speak English" also found that the teachers provided interactional feedback when addressing students in the classroom. In terms of attitude, the students had a positive attitude toward lecturer talk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The total numbers of meetings were three meetings. But according to one expert in Munawir (2011), in qualitative research, the researcher should observe in the field before doing the real research in order to know what aspects that can be researched in the real research. Thus, the total number for each class informally is four meetings.…”
Section: Instrument and Proceduresmentioning
confidence: 99%
“…It is also closely related to what Breen (1980) calls the process syllabus. Opportunities for growth Students Need Analysis on Speaking Materials: A Survey Study at SMA N 1 Bantul Zahrotul Fitri, Azwar Abbas they need more confidence (Munawir, 2017;Nasir & Dermawan, 2022). That is why we need to find out the need for analysis from these students regarding speaking.…”
Section: Introductionmentioning
confidence: 99%